Penerapan Media Monopoli Dalam Pembelajaran IPS Di Tema 5 Untuk Meningkatkan Hasil Belajar Siswa Kelas V Sekolah Dasar - Maulida Dwi Susanti; Ita Rustiati Ridwan; Susilawati (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
Social studies subjects are one of the lessons that are trained in elementary schools. The age of elementary school students is at the concrete operational stage, this situation shows that students in elementary school still find it difficult to pursue abstract learning. However, in reality, in social studies learning the teacher only uses the lecture method and does not utilize the media during the teaching and learning process. This situation makes students feel bored quickly, unmotivated and passive during the learning process so that the learning outcomes to be achieved are less than optimal. Therefore, efforts are needed in making various kinds of media so that they can be used in the learning process. This study aims to determine the application of monopoly media in social studies learning in Theme 5 to increase activity and learning outcomes for fifth grade elementary school students. The method applied in this research is Classroom Action Research (CAR) by taking the Kemmis & Mc. Taggart. The data collection instruments used in this study were interviews, observations and tests. This research was carried out in several stages, namely pre-cycle and cycle. Pre-cycle consists of observation and reflection. Meanwhile, the cycle stage includes planning, implementation, observation and reflection. The subjects in this study were fifth grade students at SDN Serang 07 with 25 members. This research is said to be successful if the indicators of success are achieved, namely the percentage of learning activities and student learning outcomes that increase or meet the target of 80% or more, and the student learning outcomes get a score of 70. The results showed that: (1) the learning activities of fifth graders experienced an increase while using monopoly media, this was evidenced by the increasing percentage, starting from the pre-cycle the percentage was 38.2%, in the first cycle it increased to 73.4%, in the first cycle it was 73.4%. the second cycle increased again to 89.4% and got very good percentage criteria, (2) the learning outcomes of class V students increased while using monopoly media, this was evidenced by the increasing percentage during the activity cycle, starting from the pre-cycle to get a percentage of 32% , in the first cycle it increased to 68%, in the second cycle it increased again to 88% and got very good percentage criteria.